2015
DOI: 10.1002/bjs.9803
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rurality, deprivation and distance from clinic on uptake in men invited for abdominal aortic aneurysm screening

Abstract: Both urban residence and social deprivation were associated independently with uptake among men invited for AAA screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…The uptake rate was variable across England and may have depended on a number of factors, including rurality and deprivation. Others have also found that deprivation and distance to travel to the screening centre affect uptake. Ensuring equality of information and access to AAA screening among men in England may mean improving communication to enhance awareness, and expanding the use of the AAA decision support tool.…”
Section: Discussionmentioning
confidence: 99%
“…The uptake rate was variable across England and may have depended on a number of factors, including rurality and deprivation. Others have also found that deprivation and distance to travel to the screening centre affect uptake. Ensuring equality of information and access to AAA screening among men in England may mean improving communication to enhance awareness, and expanding the use of the AAA decision support tool.…”
Section: Discussionmentioning
confidence: 99%
“…This is quite variable, however, and local factors, such as access to screening centres and local publicity can make a difference. 12 Second, men in deprived areas are more likely to decline to be screened. It is generally believed that the prevalence of AAA is higher in men who do not attend for AAA screening, possibly as a result of their attitude to their own health.…”
Section: Discussionmentioning
confidence: 99%
“…4 Similar studies have been reported from Sweden 15 and Scotland. 12 The links among age, social deprivation, and ethnicity are complex. Most recently, rurality (distance from the nearby city centre) has been shown to affect attendance for AAA screening, 12 but with complex local interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Access is not limited just by the screening criteria, but also by the ability and willingness of individuals to attend. It has been thought that those living more remotely or rurally would respond less frequently to screening, but this has been disproven, suggesting that response rates in smaller districts are as good if not better than those in large urban communities. Those from lower socioeconomic settings do, however, respond less frequently.…”
mentioning
confidence: 99%
“…Measures to improve response rates are always a challenge to screening programmes. Inviting people to be screened at smaller local units appears to improve attendance compared with attending more centralized locations.…”
mentioning
confidence: 99%